Dyes Used for Colouring Manuscripts and Their Effect on Cellulose Degradation - Akyol, Emel; Sevim, Pinar Cakar (WALTER DE GRUYTER GMBH, 2023)
Manuscripts are one of the most important cultural heritage objects that not only contain essential information, but also provide valuable insights into the social, cultural, and economic conditions of the era in which they were written. These materials are subject to degradation over time due to both internal and external factors. While ageing processes of pure cellulose or the effect of iron gall ink on cellulose have been studied extensively, there is little known about deterioration mechanisms in dyed paper. In this study, safflower (Carthamus tinctorius L.), buckthorn (Rhamnus petiolaris Boiss), turmeric (Curcuma longa L.), and onion peel (Allium cepa L.) plants as well as cochineal insect (Dactylopius coccus Costa) extracts were used to dye Whatman filter papers. Samples were then subjected to accelerated ageing to determine the long-term effects of the dyes. Colour, pH, viscosity, and glycosidic bond breakage rates were measured before and after ageing. Onion peel dyed paper exhibited the highest rates of degradation, followed by buckthorn, cochineal, safflower, and turmeric-dyed paper. The alum and tannin content may have caused the degradation. The findings of this work may provide conservators with valuable scientific data on the effect of dyes on the degradation kinetics of cellulose.
Keywords: degradation kinetics; degree of polymerisation; cellulose; natural dye; manuscript; IRON GALL INK; SIZE-EXCLUSION CHROMATOGRAPHY; PAPER; STABILIZATION; Information Science & Library Science